Tip of the Iceberg? Country- and Company-Level Analysis of Drug Company Payments for Research and Development in Europe - Piotr Ozieranski; Luc Martinon; Pierre-Alain Jachiet; Shai Mulinari (Kerman University of Medical Sciences, 2022)
Background  Creating new therapies often involves drug companies paying healthcare professionals and institutions for research and development (R&D) activities, including clinical trials. However, industry sponsorship can create conflicts of interest (COIs). We analysed approaches to drug company R&D payment disclosure in European countries and the distribution of R&D payments at the country and company level.Methods  Using documentary sources and a stakeholder survey we identified country- regulatory approaches to R&D payment disclosure. We reviewed company-level descriptions of disclosure practices in the United Kingdom, a country with a major role in Europe's R&D. We obtained country-level R&D payment data from industry trade groups and public authorities and company-level data  from eurosfordocs.eu, a publicly available payments database. We conducted content analysis and descriptive statistical analysis.Results  In 32 of 37 studied countries, all R&D payments were reported without named recipients, following a selfregulatory approach developed by the industry. The methodological descriptions from 125 companies operating in the United Kingdom suggest that within the self-regulatory approach companies had much leeway in deciding what activities and payments were considered as R&D. In five countries, legislation mandated the disclosure of R&D payment recipients, but only in two were payments practically identifiable and analysable. In 17 countries with available data, R&D constituted 19%-82% of all payments reported, with self-regulation associated with higher shares. Available companylevel data from three countries with self-regulation suggests that R&D payments were concentrated by big funders, and some companies reported all, or nearly all, payments as R&D.Conclusion  The lack of full disclosure of R&D payments in countries with industry self-regulation leaves considerable sums of money unaccounted for and potentially many COIs undetected. Disclosure mandated by legislation exists in few countries and rarely enhances transparency practically. We recommend a unified European approach to R&D payment disclosure, including clear definitions and a centralised database.